2009
DOI: 10.1093/annonc/mdn719
|View full text |Cite
|
Sign up to set email alerts
|

Neo-adjuvant treatment of rectal cancer with capecitabine and oxaliplatin in combination with radiotherapy: a phase II study

Abstract: CAP-OX-RT as preoperative treatment for rectal cancer induces a remarkable rate of complete or near-complete pathologically documented response and is well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…Following preoperative CRT, TRG scores may reflect the characteristics of proliferation and resistance to hypoxia of residual cancer cells [35] [37]. TRG was reported to have prognostic value in LARC patients after preoperative CRT, and has also been previously reported as an independent prognostic factor for local recurrence [5,38,39].…”
Section: Discussionmentioning
confidence: 95%
“…Following preoperative CRT, TRG scores may reflect the characteristics of proliferation and resistance to hypoxia of residual cancer cells [35] [37]. TRG was reported to have prognostic value in LARC patients after preoperative CRT, and has also been previously reported as an independent prognostic factor for local recurrence [5,38,39].…”
Section: Discussionmentioning
confidence: 95%
“…This analysis involved patients enrolled in a phase II trial, whose entry criteria and main results have been reported elsewhere [25]. Briefly, 46 patients with a histologic diagnosis of rectal adenocarcinoma invading the intestinal wall or with pelvic lymph node involvement were treated preoperatively with 2 cycles of capecitabine and oxaliplatin combined with pelvic conformal radiotherapy (45 Gy in 5 weeks).…”
Section: Methodsmentioning
confidence: 99%
“…21 The addition of a second chemotherapeutic agent to neoadjuvant capecitabine-based CRT with cetuximab has not demonstrated a marked improvement to the rates of pCR or tumor downstaging in LARC, 24 which remain similar to those reported from studies of neoadjuvant capecitabine-based CRT, 12,13,25 or capecitabine-based CRT with irinotecan or oxaliplatin. 26,27 In the present study an assessment of radiological tumor response according to RECIST criteria was made. An overall response rate of 71% was recorded, which was similar to the that reported for patients with locally advanced SCCHN receiving cetuximab in combination with radiotherapy.…”
Section: Neoadjuvant Cetuximab Plus Crt On Tumor Response In Larcmentioning
confidence: 99%